Exploring the fate of inhaled monoclonal antibody in the lung parenchyma by microdialysis. Issue 2 (17th February 2019) - Guillon, Antoine; Pardessus, Jeoffrey; Lhommet, Pierre; Parent, Christelle; Respaud, Renaud; Marchand, Denis; Montharu, Jérôme; De Monte, Michèle; Janiak, Philip; Boixel, Christophe; Audat, Héloïse; Huille, Sylvain; et al.
ABSTRACT: Therapeutic antibodies (Abs) are emerging as major drugs to treat respiratory diseases, and inhalation may provide substantial benefits for their delivery. Understanding the behavior of Abs after pulmonary deposition is critical for their development. We investigated the pharmacokinetics of a nebulized Ab by continuous sampling in lung parenchyma using microdialysis in non-human primates. We defined the optimal conditions for microdialysis of Ab and demonstrated that lung microdialysis of Ab is feasible over a period of several days. The concentration-profile indicated a two-phase non-linear elimination and/or distribution of inhaled mAbX. Lung exposition was higher than the systemic one over a period of 33 hours and above MabX affinity for its target. The microdialysis results were supported by an excellent relationship with dosages from lung extracts.